Robots, Reshoring, and the Lot of Low-Skilled Workers - Astrid Krenz; Holger Strulik; Klaus Prettner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We propose a theoretical framework to analyze the offshoring and reshoring decisions of firms in the age of automation. Our theory suggests that increasing productivity in automation leads to a relocation of previously offshored production back to the home economy but without improving low-skilled wages and without creating jobs for low-skilled workers. Since it leads also to increasing wages for high-skilled workers, automation induced reshoring is associated with an increasing skill premium and increasing inequality. We develop a measure for reshoring activity at the macro-level and, using data from the world input output table, we provide evidence for automation-driven reshoring. On aver- age, within manufacturing sectors, an increase by one robot per 1000 workers is associated with a 3.5% increase of reshoring activity. We also provide the first cross-country evidence that reshoring is positively associated with wages and employment for high-skilled labor but not for low-skilled labor.
Keywords: F13; F62; J31; O33; 330; Automation; Reshoring; Employment; Wages; Inequality; Tariffs